Association between biomarkers of tissue inflammation and progression of osteoarthritis: evidence from the Rotterdam study cohort. Issue 1 (December 2016) - Saberi Hosnijeh, Fatemeh; Siebuhr, Anne; Uitterlinden, Andre; Oei, Edwin; Hofman, Albert; Karsdal, Morten; Bierma-Zeinstra, Sita; Bay-Jensen, Anne; van Meurs, Joyce
Abstract Background We aimed to investigate the prognostic value of two biomarkers of tissue inflammation, matrix metalloproteinase-dependent degradation of C-reactive protein (CRPM) and connective tissue type I collagen turnover (C1M), on the incidence and progression of radiographic osteoarthritis (OA) in the Rotterdam Study, a prospective cohort. Moreover, the independent effect of these biomarkers with respect to the established biomarkers of OA progression, like urinary type II collagen degradation (uCTX-II) and serum cartilage oligomeric protein (COMP), was evaluated. Methods Serum levels of C1M, CRPM, COMP and CRP of 1335 participants aged >55 years were measured in fasting serum using ELISA. The commercial ELISA detecting CTX-II was used in urine. Radiographs at baseline and 5-year follow-up were scored for OA stage by Kellgren-Lawrence grade. The associations between progression and incidence of OA and the baseline biomarkers were examined using logistic regression and generalized estimating equations adjusted for age, sex, BMI, and possible other confounders. Results The uCTX-II, COMP, and CRP concentrations were associated with the incidence and progression of OA. Moreover, OA progression was positively associated with CRPM (OR = 1.3, p  = 0.01) and CRP (OR = 1.3, p  = 0.01) levels with similar effect size as uCTX-II (OR = 1.3, p  = 0.01) and COMP (OR = 1.2, p  = 0.02). CRPM had prognostic value for progression of OA independent from the uCTX-II and COMP. Conclusions Our study confirmed the associations between uCTX-II and COMP concentrations and OA progression. Importantly, we showed for the first time that CRPM predicts the risk of OA progression independent of the established biomarkers uCTX-II and COMP.